Laparoscopic resection of functional non communicating rudimentary horn of uterus in adolescent girl - Aggarwal, Ramita; Kaur, Jagpreet; Gupta, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Unicornuate uterus with rudimentary horn is a rare type of mullerian anomaly associated with many obstetrical and gynaecological complications. The incidence is approximately 1:100000. Author reports a case of 18-year-old unmarried female with unicornuate uterus with non-communicating and functional rudimentary horn presented with chief complaint of refractory dysmenorrhea.